2023
DOI: 10.3389/fneur.2023.1086622
|View full text |Cite
|
Sign up to set email alerts
|

Ethiopians' knowledge of and attitudes toward epilepsy: A systematic review and meta-analysis

Abstract: BackgroundEpilepsy remains one of the world's most common neurological diseases, but it appears to be widely misunderstood, particularly in under-resourced countries like Ethiopia. Improving individuals' knowledge and attitude toward epilepsy is critical for reducing the multifaceted impacts of epilepsy. Therefore, in this study, we sought to estimate the pooled levels of good knowledge and a favorable attitude toward epilepsy and also identify the associated factors using available data collected from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The availability and affordability of antiseizure medications, which are crucial for managing epilepsy, often face challenges [ 34 ]. Additionally, misconceptions and cultural beliefs contribute to stigmatizing individuals with epilepsy, which hinders their acceptance and access to healthcare services [ 12 , 13 , 35 ]. As a result, epilepsy management in Ethiopia is suboptimal, leading to inadequate seizure control and negatively impacting the affected individuals’ quality of life [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability and affordability of antiseizure medications, which are crucial for managing epilepsy, often face challenges [ 34 ]. Additionally, misconceptions and cultural beliefs contribute to stigmatizing individuals with epilepsy, which hinders their acceptance and access to healthcare services [ 12 , 13 , 35 ]. As a result, epilepsy management in Ethiopia is suboptimal, leading to inadequate seizure control and negatively impacting the affected individuals’ quality of life [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different cultural backgrounds influence the treatment of epilepsy by shaping beliefs, stigmas, and cultural practices, which in turn impact medical accessibility, treatment adherence, and social integration [ 10 , 11 ]. In Ethiopia, cultural beliefs and practices often result in the use of traditional medicine, religious rituals, or misconceptions about epilepsy, which can hinder access to appropriate medical treatments and result in the stigmatization of individuals living with epilepsy [ 6 , 8 , 12 , 13 ]. Additionally, resource-limited countries face challenges related to climate change, such as global warming, that can adversely affect the accessibility and availability of antiseizure medications and hinder seizure control [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three of the studies reported that 47.5% of participants did not want to allow PWE to study at school with healthy people 37,39,40 . The unfavorable attitudes and practices might be directly attributed to the participants' educational level and sociocultural influences and their low access to health educational programs 47–49 . People's preference for traditional and cultural practices likely originates from their beliefs in unearthly/mystic causes of epilepsy to be intervened through educational campaigns.…”
Section: Discussionmentioning
confidence: 99%